Costumer Satisfaction On Wedding Organizer During The Covid-19 Pandemic (Adinata Wedding Organizer Case Study) - Sefina Isna Asaroh; Mar'atul Fahimah (INCOME: Innovation of Economics and Management, 2022)
This study aims to determine the influence of people, process, and physical evidence on costumer satisfaction at adinata wedding organizers during the covid-19 pandemic. This type of research is associative research. with the form of research is a quantitative approach. the sampling technique used purposive sampling, the respondents of this study were contumers who used the services of a wedding organizer from March 12, 2020 to June 12, 2021 with a total sample of 40 respondents. Data collection techniques using the method of observation and questionnaires. The research instrument used in this study was a questionnaire (Questionnaire). The data analysis technique in this study uses multiple linear regression, partial T test and simultaneous F test, the data is processed using the SPSS 26 program. The results of this research show that there is no significant effect of people on costumer satisfaction, while process has a significant effect on customer satisfaction. and physical evidence has a significant influence on contumer icon satisfaction in choosing Adinata wedding organizer services during the covid-19 pandemic.